2021
DOI: 10.1111/prd.12384
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid‐derived suppressor cells in obesity‐associated periodontal disease: A conceptual model

Abstract: Periodontitis is a common chronic inflammatory disease characterized by destruction of the supporting structures of the teeth. Severe periodontitis is highly prevalent—affecting 10%‐15% of adults—and carries several negative comorbidities, thus reducing quality of life. Although a clear relationship exists between severity of obesity and incidence of periodontal disease, the biologic mechanisms that support this link are incompletely understood. In this conceptual appraisal, a new “two‐hit” model is presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…M1 macrophages caused alveolar bone damage by producing matrix metalloproteinases (MMPs) and prostaglandin E2 (PGE2), and M2 macrophages relieved inflammation and repaired periodontium by secreting IL‐10 and TGF‐β 47 . Additionally, MDSCs could contribute to the establishment and development of periodontitis not only through increasing the quantity and activity of osteoclasts, but also through exerting immune suppression 48,49 . It should be kept in mind that certain immunocytes are double‐edged swords in periodontitis, which can play different or even opposite roles in diverse stages of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages caused alveolar bone damage by producing matrix metalloproteinases (MMPs) and prostaglandin E2 (PGE2), and M2 macrophages relieved inflammation and repaired periodontium by secreting IL‐10 and TGF‐β 47 . Additionally, MDSCs could contribute to the establishment and development of periodontitis not only through increasing the quantity and activity of osteoclasts, but also through exerting immune suppression 48,49 . It should be kept in mind that certain immunocytes are double‐edged swords in periodontitis, which can play different or even opposite roles in diverse stages of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that macrophages and osteoclasts share the same myeloid cell lineage and common monocytic cell embryology [ 121 ]. Recently, Kwack et al [ 122 ] postulated a conceptual “two-hit” model to explain obesity-exacerbated alveolar bone destruction, namely that obesity expands specific myeloid progenitor subpopulations (first hit), then is transported to the periodontal inflammatory site to differentiate into monocytes (osteoclasts) which led to obesity-associated alveolar bone loss (second hit) in a context-dependent manner ( Figure 1 , lower panel).…”
Section: Mechanisms By Which Obesity Enhances Periodontal Bone Lossmentioning
confidence: 99%
“…In acute infections, it is proposed that MDSCs may have a beneficial role when the stimulus has been cleared by limiting tissue damage produced for a persistent immune response [ 9 ]. In contrast, during chronic inflammation, expansion and activation of MDSCs contribute to immunosuppression and oxidative stress [ 10 , 11 ]. However, differentiation and function of MDSCs are influenced by the inflammatory microenvironment generated, suggesting a disease-specific function of MDSCs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent publications have reported that MDSCs can function as osteoclast progenitors in pathological conditions with complications associated with bone destruction [ 10 , 11 , 15 , 16 ], including collagen-induced arthritis models [ 17 ]. However, no studies have addressed MDSCs in the context of osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation